CD4-Binding Site Directed Cross-Neutralizing scFv Monoclonals from HIV-1 Subtype C Infected Indian Children - Kumar, Sanjeev; Kumar, Rajesh; Khan, Lubina; Makhdoomi, Muzamil Ashraf; Thiruvengadam, Ramachandran; Mohata, Madhav; Agarwal, Mudit; Lodha, Rakesh; Kabra, Sushil Kumar; Sinha, Subrata; Luthra, Kalpana (Frontiers in Immunology, 2017)
Progression of human immunodeficiency virus-1 (HIV-1) infection in children is faster than adults. HIV-1 subtype C is responsible for more than 50% of the infections globally and more than 90% infections in India. To date, there is no effective vaccine against HIV-1. Recent animal studies and human Phase I trials showed promising results of the protective effect of anti-HIV-1 broadly neutralizing antibodies (bnAbs). Interaction between CD4bs on the HIV-1 envelope glycoprotein and CD4 receptor on the host immune cells is the primary event leading to HIV-1 infection. The CD4bs is a highly conserved region, comprised of a conformational epitope and is a potential target of bnAbs such as VRC01 that is presently under human clinical trials. Recombinant scFvs can access masked epitopes due to their small size and have shown the potential to inhibit viral replication and neutralize a broad range of viruses. Pediatric viruses are resistant to many of the existing bnAbs isolated from adults. Therefore, in this study, pooled peripheral blood mononuclear cells from 9 chronically HIV-1 subtype C infected pediatric cross-neutralizers whose plasma antibodies exhibited potent and cross-neutralizing activity, were used to construct a human anti-HIV-1 scFv phage library of 9×108 individual clones. Plasma mapping using CD4bs specific probes identified the presence of CD4bs directed antibodies in 4 of these children. By extensive biopanning of the library with CD4bs specific antigen RSC3 core protein, we identified two cross-neutralizing scFv monoclonals 2B10 and 2E4 demonstrating a neutralizing breadth and GMT of 77%, 17.9µg/ml and 32%, 51.2µg/ml respectively, against a panel of 49 tier 1, 2 and 3 viruses. Both scFvs competed with anti-CD4bs bnAb VRC01 confirming their CD4bs epitope specificity. The 2B10 scFv was effective in neutralizing the 7 subtype C and subtype A pediatric viruses tested. Somatic hypermutations (SHM) in the VH gene of scFvs (10.1%-11.1%) is comparable with that of the adult antibodies. These cross-neutralizing CD4bs directed scFvs can serve as potential reagents for passive immunotherapy. A combination of cross-neutralizing scFvs of diverse specificities with antiretroviral drugs may be effective in suppressing viremia at an early stage of HIV-1 infection and prevent disease progression.